Mission in Central and Eastern Europe : realities, perspectives, trends /. - Constantineanu, Corneliu; Macelaru, Marcel V.; Kool , Anne-Marie.; Himcinschi, Mihai (Oxford. : : Regnum Books International, 2016)
The present volume brings together significant contributions from over thirty theologians, missiologists and practitioners from this part of the world. The articles explore the complex missiological thinking and praxis of Central and Eastern Europe, highlight concrete missiological endeavours and pointing to the challenges and opportunities for mission in this part of the world. It also includes relevant missiological documents that emerged in the area within the past 25 years."--Back cover.
The kingdom of God and the kingdoms of the world: church-state relationships in the context of the Romanian totalitarian political regime / Christianity with and for the younger generation: a case study in Orthodox youth mission / The future of Orthodox Christianity in the context of a theology of integrity: a perspective from Serbia / The story of the Lausanne-Orthodox Initiative: a personal perspective / Foundations for mission in the Greek-Catholic Church from Romania / Mission in Poland: a Roman Catholic perspective / The mission of the church in Poland after political transformation / The encounter between Christianity and Islam in Bosnia and Herzegovina: a missiological perspective / .
Includes bibliographical references and index.
Keywords: Missions -- Europe, Central; Missions -- Europe, Eastern